Report on the 1964 Annual Meeting of the Society of Ethnomusicology - Nettl, Bruno (International Library of African Music, 1964)
The paper which was greeted with most enthusiasm was Eric Werner’s, which questioned some of the fundamental precepts of our field. In general, it seemed to be the concensus of some of the participants that the last ten years have yielded a tremendous increase in quantity of research, but that the fundamental views of the researchers have not changed much.
Keywords: African Music